KINERJA PENDAMPING PROGRAM KELUARGA HARAPAN (PKH) DI KECAMATAN KAMPAR KABUPATEN KAMPAR TAHUN 2019 - ", Kafriliasari; SD, Zaili Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Poverty that occurs in Indonesia is a problem that must be resolved immediately. Poverty that occurs if not handled seriously will have a prolonged impact. The Conditonal Cash Transfer (CCT) is a national program that has been implemented since 2007 by the Indonesian Ministry of Social Affairs. The form of this program is the provision of cash assistance (cast transfer) to KSM receiving aid. The performance of PKH Facilitators in implementing this program greatly determines the sustainability and success of this program, either directly or indirectly. PKH Facilitators as parties who are in direct contact with beneficiary families (KPM) hold meetings, see their living conditions directly, provide motivation, and seek the best solutions if the beneficiary families (KPM) experience problems. The theory used in this study is the Mangkunegara theory which includes performance indicators, namely: quality of work, quantity of work, implementation of duties and responsibilities. The research method used is descriptive qualitative with data collection techniques through interviews, observation and documentation. Selection of research informants using the snowball sampling technique. The results of this study indicate that the performance of PKH facilitators in Kampar sub-district, Kampar district in 2019 is arguably good because the facilitators have carried out PKH activities according to their duties and responsibilities, but not all PKH facilitators have performed well but there are also companions. PKH which has weak performance.Â Keywords : Performance, Fasilitators, Conditonal Cash Transfer (CCT)